2014
DOI: 10.1002/ajmg.a.36802
|View full text |Cite
|
Sign up to set email alerts
|

Association between NOGGIN and SPRY2 polymorphisms and nonsyndromic cleft lip with or without cleft palate

Abstract: Nonsyndromic cleft lip with or without cleft palate (NSCLP) is a common congenital malformation with a worldwide prevalence rate of 0.4-2.0% among live births, depending on race and ethnic background. Single-nucleotide polymorphisms (SNPs) of genes may contribute to NSCLP risk, although the risk factors and pathogenesis of NSCLP remain unknown. The objective of this study was to investigate association of SNPs of noggin (NOG) and sprouty homolog 2 (SPRY2) with NSCLP risk. A total of 188 NSCLP patients and 228 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…This interaction with the BMP signaling may be the key point to explain a possible association between SMURF1 and OFC etiology, as two members of this pathway, BMP2 and BMP4 , are already known to be associated with OFCs (Supplementary Table 2) (Zhang et al 2002 ; Liu et al 2005 ; Marazita 2007 ; Lin et al 2008 ; Suzuki et al 2009 ; Suazo et al 2010 ; Sahoo et al 2011 ; Williams et al 2012 ). SPRED1 , recognized as the causative gene for Legius syndrome (OMIM #611431), interacts with SPRY2 that has been described as a causative OFC gene (Supplementary Table 2) (Vieira et al 2005 ; Goodnough et al 2007 ; Welsh et al 2007 ; Spurlock et al 2009 ; Matsumura et al 2011 ; Song et al 2015 ). In addition, SPRED1 and SPRY2 act as negative regulators of the FGF and MAPK pathways (Katoh and Katoh 2006 ; Di Bari et al 2009 ; Sylvestersen et al 2011 ; Zhao et al 2015 ), both shown to affect orofacial development in human or in mouse models (Reardorn et al 1994 ; Wilkie et al 1995 ; Sasaki et al 2001 ; Dodé et al 2003 ; Yamamoto et al 2003 ; Riley and Murray 2007 ; Singh et al 2007 ; Newbern et al 2008 ; Nakamura et al 2009 ; García-Domínguez et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…This interaction with the BMP signaling may be the key point to explain a possible association between SMURF1 and OFC etiology, as two members of this pathway, BMP2 and BMP4 , are already known to be associated with OFCs (Supplementary Table 2) (Zhang et al 2002 ; Liu et al 2005 ; Marazita 2007 ; Lin et al 2008 ; Suzuki et al 2009 ; Suazo et al 2010 ; Sahoo et al 2011 ; Williams et al 2012 ). SPRED1 , recognized as the causative gene for Legius syndrome (OMIM #611431), interacts with SPRY2 that has been described as a causative OFC gene (Supplementary Table 2) (Vieira et al 2005 ; Goodnough et al 2007 ; Welsh et al 2007 ; Spurlock et al 2009 ; Matsumura et al 2011 ; Song et al 2015 ). In addition, SPRED1 and SPRY2 act as negative regulators of the FGF and MAPK pathways (Katoh and Katoh 2006 ; Di Bari et al 2009 ; Sylvestersen et al 2011 ; Zhao et al 2015 ), both shown to affect orofacial development in human or in mouse models (Reardorn et al 1994 ; Wilkie et al 1995 ; Sasaki et al 2001 ; Dodé et al 2003 ; Yamamoto et al 2003 ; Riley and Murray 2007 ; Singh et al 2007 ; Newbern et al 2008 ; Nakamura et al 2009 ; García-Domínguez et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, Lewis et al () demonstrated that the GREM1 enhancer at rs16969681 plays an important role in cells of epithelial origin (Lewis et al, ). In humans, the chromosomal region 17q22 containing the NOG gene is significantly correlated with the risk of oral clefts (Mangold et al, ; Figueiredo et al, ; Song et al, ). Evidence for the involvement of this locus in the NSCL/P etiology was also found in a sample from the Polish population (Mostowska et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The other BMP antagonist, Noggin (NOG), regulates the BMP signal, which is required to maintain the palatal epithelium integrity. There was evidence that lacking NOG gene caused a cleft palate in mice, while in humans, our research team and other studies have discovered that NOG on chromosome 17q22 was linked to the occurrence of CL/P . In this study, the BMP antagonist GREM1 gene was also identified as a susceptibility gene of NSOC.…”
Section: Discussionmentioning
confidence: 55%